2017
DOI: 10.1158/0008-5472.can-16-1454
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Receptor–Mediated Internalization of Imaging Agents Detects Epithelial Ovarian Cancer with Enhanced Sensitivity and Specificity

Abstract: Poor prognosis of ovarian cancer (OvCa), the deadliest of the gynecologic malignancies, reflects major limitations associated with detection and diagnosis. Current methods lack high sensitivity to detect small tumors and high specificity to distinguish malignant from benign tissue, both impeding diagnosis of early and metastatic cancer stages and leading to costly and invasive surgeries. Tissue microarray analysis revealed that >98% of OvCa express the prolactin receptor (PRLR), forming the basis of a new mole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…This study found that human FTE actually produce their own PRL as well as many HGSOC cell lines, thus PRL as a biomarker might be a reflection of the fallopian tube origin. In addition to the ligand, MRI or infrared fluorescence imaging bioconjugates were previously designed that specifically bind to the PRL-R [39]. These conjugates effectively underwent selective internalization and facilitated the PRL-R targeted diagnosis of ovarian cancer [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that human FTE actually produce their own PRL as well as many HGSOC cell lines, thus PRL as a biomarker might be a reflection of the fallopian tube origin. In addition to the ligand, MRI or infrared fluorescence imaging bioconjugates were previously designed that specifically bind to the PRL-R [39]. These conjugates effectively underwent selective internalization and facilitated the PRL-R targeted diagnosis of ovarian cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ligand, MRI or infrared fluorescence imaging bioconjugates were previously designed that specifically bind to the PRL-R [39]. These conjugates effectively underwent selective internalization and facilitated the PRL-R targeted diagnosis of ovarian cancer [39]. Therefore, both the ligand and the receptor of prolactin are not simply biomarkers, but also active drivers of fallopian tube derived HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…False-positive lymph nodes were also observed in a phase II trial of OTL38 in ovarian cancer (21). Sundaram reported a prolactin receptor-specific probe using placental lactogen (hPL) conjugated to MRI and NIRF imaging agents and showed improved specificity over currently used contrast agents (11). However, continuous exposure (16 days) to hPL conjugates caused increased activity in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since ovarian cancer has a peritoneal dissemination pattern, imaging agents can bind to malignant lesions more directly through peritoneal injection. Several studies have testified the viability of the peritoneal administration of imaging agents for detecting peritoneal metastasis (11,33,34). Nonetheless, systemic administration of the probe will be attempted to detect distant metastasis or deep lesions in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation